Understanding gender dynamics in mHealth interventions can enhance the sustainability of benefits of digital technology for maternal healthcare in rural Nigeria - Udenigwe, Ogochukwu; Okonofua, Friday E.; Ntoimo, Lorretta F. C.; Yaya, Sanni (Frontiers in Global Women's Health, 2022)
Introduction Nigeria faces enormous challenges to meet the growing demands for maternal healthcare. This has necessitated the need for digital technologies such as mobile health, to supplement existing maternal healthcare services. However, mobile health programs are tempered with gender blind spots that continue to push women and girls to the margins of society. Failure to address underlying gender inequalities and unintended consequences of mobile health programs limits its benefits and ultimately its sustainability. The importance of understanding existing gender dynamics in mobile health interventions for maternal health cannot be overstated. Objective This study explores the gender dimensions of Text4Life, a mobile health intervention for maternal healthcare in Edo State, Nigeria by capturing the unique perspectives of women who are the primary beneficiaries, their spouses who are all men, and community leaders who oversaw the implementation and delivery of the intervention. Method This qualitative study used criterion-based purposive sampling to recruit a total of 66 participants: 39 women, 25 men, and two ward development committee chairpersons. Data collection involved 8 age and sex desegregated focus group discussions with women and men and in-depth interviews with ward development committee chairpersons in English or Pidgin English. Translated and transcribed data were exported to NVivo 1.6 and data analysis followed a conventional approach to thematic analysis. Results Women had some of the necessary resources to participate in the Text4Life program, but they were generally insufficient thereby derailing their participation. The program enhanced women's status and decision-making capacity but with men positioned as heads of households and major decision-makers in maternal healthcare, there remained the possibility of deprioritizing maternal healthcare. Finally, while Text4Life prioritized women's safety in various contexts, it entrenched systems of power that allow men's control over women's reproductive lives. Conclusion As communities across sub-Saharan Africa continue to leverage the use of mHealth for maternal health, this study provides insights into the gender implications of women's use of mHealth technologies. While mHealth programs are helpful to women in many ways, they are not enough on their own to undo entrenched systems of power through which men control women's access to resources and their reproductive and social lives.